Batch and Flow Synthesis of Disulfides by Visible-Light-Induced TiO2 Photocatalysis - Bottecchia, Cecilia; Erdmann, Nico; Tijssen, Patricia M. A.; Milroy, Lech-Gustav; Brunsveld, Luc; Hessel, Volker; Noël, Timothy (ChemSusChem, 2016)
A mild and practical method for the preparation of disulfides through visible‐light‐induced photocatalytic aerobic oxidation of thiols has been developed. The method involves the use of TiO2 as a heterogeneous photocatalyst. The catalyst's high stability and recyclability makes this method highly practical. The reaction can be substantially accelerated in a continuous‐flow packed‐bed reactor, which enables a safe and reliable scale‐up of the reaction conditions. The batch and flow protocol described herein can be applied to a diverse set of thiol substrates for the preparation of homo‐ and hetero‐dimerized disulfides. Furthermore, biocompatible reaction conditions (i.e., room temperature, visible light, neutral buffer solution, and no additional base) have been developed, which permits the rapid and chemoselective modification of densely functionalized peptide substrates without recourse to complex purification steps. S−S without the mess! A mild and practical method for the preparation of disulfides through visible‐light‐induced photocatalytic aerobic oxidation of thiols is described. The method involves the use of TiO2 as a heterogeneous photocatalyst, which provides high stability and recyclability. The batch and flow protocol can be applied to a diverse set of thiol substrates for the preparation of homo‐ and hetero‐dimerized disulfides and can be used for peptide modification.